The role of soybeans on hemoglobin levels in pregnant women Tangerang City in 2022 - Afrilia, Eka Mardiana; Musa, Siti Mardhatillah; Wahidin; Lestari, Murni; Rahmawati, Diyah Tepi (MEDIA ILMU KESEHATAN, 2024)
Background: Anemia in pregnancy is a condition affecting around 70% of pregnant women in Indonesia due to factors such as iron deficiency, vitamin B12 deficiency, and vitamin C deficiency. Soybeans can be an alternative food to prevent anemia in pregnant women, as they are a vital source of health.Objective: To determine the benefits and effects of consuming processed soybean foods on hemoglobin levels in mothers during pregnancy.Method: The study utilized a quasi pre-experimental approach with a pretest-posttest approach to analyze data from 25 pregnant women at Azzahra 2 Clinic Tangerang from July to August in 2022.Results:The results showed that after consuming processed soybean food, pregnant women's hemoglobin levels increased from 10 g/dl to 10.5 g/dl. The effect of giving processed soybean food on hemoglobin in pregnant women at Az-Zahra Clinic 2 Tangerang City was significant (p-value= 0.000 < 0.05).Conclusion: The study concluded that there is a relationship between the provision of processed soybeans and increasing hemoglobin levels in pregnant women. Pregnant women can consume processed soy foods as an alternative to traditional diets.